Improving Speaking Performance Through Pecha Kucha Presentation Method - Sevirda Arniatika (Jurnal Pedagogy, 2018)
The objective of this research is to show the improvement of the students’ speaking performance using Pecha Kucha presentation method among the tenth graders of SMA Muhammadiyah East Lampung. The research method used in this research is a Classroom Action Research (CAR) which is used to solve the students’ problem in speaking performance. The subjects of this research are X MIA students of SMA Muhammadiyah Pekalongan East Lampung in the academic year of 2017/2018. The research instruments used to collect the data in this research are test, observation and documentation. The result of this research shows that the implementation of Pecha Kucha presentation method is successful since the criteria of success are achieved. The first criterion is 70% of the students could pass the target score ≥ 70 based on the KKM. The finding shows that 77.78% of the students had already achieved the target score. Besides, the second criterion is the students who became more active in the learning process. The result of observation shows that by using Pecha Kucha presentation method, most of the students are involved actively in the learning process.